Experimental testing of thermal house for different weather conditions in Bale robe. (2018) - Ravi, D.; yohannes, Samson; Somanath, B; Rao, Kante Mallikarjuna; Ranganath, L.; Koteswararao, B.
Abstract: The effect of globalization can be seen all-over the world, people are locomoting from one part of the world to other. Due to this the survival became bit difficult in communities, diet etc. This paper is focused on one of those concept regarding construction of houses in Ethiopia (in the horn of Africa). A whopping number of Indian's are migrating to Ethiopia for survival with their families now-a-days. The temperature and climatic conditions vary with respect to time. Especially in robe region the temperature sometimes hits-8 0c. The adults in the range 30-40(age) can survive with some external accessories, whereas kids it's very hard for them. We are focusing in this issue and suggesting two different modes of house plans which can reduce the effect. We are justifying these houses with experimental analysis with different constraints for ten days in all seasons. Case 1 will be on cement & soil mixture house and case II will be on wood, agricultural wastage and soil. These two cases will be compared then results will be opted on constructional time, cost, easiness and maintaince. Our report concludes the best survival plan house which will full fill in all aspects. The experiments/ observations are conducted in robe region, it may not be same for all regions in Ethiopia.